Rujub, the Juggler - Henty, G. A. (George Alfred), 1832-1902 (Salt Lake City, UT : Project Gutenberg, 2005)
"Rujub, the Juggler" by G. A. Henty is a historical novel aimed at young adults and older readers, written during the late 19th century. The story is set against the backdrop of the Sepoy Mutiny in India between 1857 and 1859, focusing on the conflict between British colonial forces and Indian soldiers. The central character, Ralph Bathurst, is portrayed as a soldier who grapples with his fears and insecurities in the face of war, while Rujub, the titular juggler, serves as a mysterious and skilled ally in his journey. At the start of the narrative, readers are introduced to a festive scene at the Rajah's palace amid colorful lanterns and music, symbolizing a superficial peace before the coming turmoil. The Rajah entertains British officers, masking his underlying schemes against them while plotting with his allies to incite the Sepoy rebellion. Ralph Bathurst, on the other hand, is depicted as a natural coward who strives to prove his bravery. The opening chapters lay the groundwork for the novel$1 (Bs exploration of personal courage and friendship through the lens of historical conflict, establishing both Bathurst's struggles with his inner demons and Rujub's role as a pivotal figure, connecting traditions of Indian mystique with the unfolding drama of war. (This is an automatically generated summary.)s
Release date is 2005-01-01
Martin Robb, and David Widger
Keywords: India -- History -- Sepoy Rebellion, 1857-1858 -- Fiction